2021
DOI: 10.1186/s13287-021-02213-z
|View full text |Cite
|
Sign up to set email alerts
|

Correction to: Human embryonic stem cell-derived extracellular vesicles alleviate retinal degeneration by upregulating Oct4 to promote retinal Müller cell retrodifferentiation via HSP90

Abstract: An amendment to this paper has been published and can be accessed via the original article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…It is well known that HSP90 is secreted from cells by exosomes [ 12 ]. HSP90 in human embryonic stem cell-derived extracellular vesicles (exosomes) was shown to alleviate retinal degeneration by promoting retinal Müller cell retrodifferentiation [ 39 ]. Although increasing evidence suggests that HSP90 participates in cardioprotection against I/R, no study has addressed the function of HSP90 in exosomes induced by RIPC.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that HSP90 is secreted from cells by exosomes [ 12 ]. HSP90 in human embryonic stem cell-derived extracellular vesicles (exosomes) was shown to alleviate retinal degeneration by promoting retinal Müller cell retrodifferentiation [ 39 ]. Although increasing evidence suggests that HSP90 participates in cardioprotection against I/R, no study has addressed the function of HSP90 in exosomes induced by RIPC.…”
Section: Discussionmentioning
confidence: 99%
“…Exosomes derived from hESCs (hESCs-exo) carry hESC-specific miRNAs, mRNAs, and proteins, offering the regenerative potential of hESCs while avoiding their immune and ethical problems [24]. Therefore, hESCs-exo have emerged as critical mediators in providing an alternate cell-free therapeutic modality [25][26][27]. Several studies have shown that exosomes from embryonic stem cells can reduce inflammation and pyroptosis, such as increasing the expressions of the anti-inflammatory cytokines IL-10, IL-4, IL-9, and IL-13 [28,29] and reducing pyroptosis in doxorubicin-induced cardiomyopathy [29].…”
Section: Introductionmentioning
confidence: 99%